Sistem Pemanfaatan Hashtag(#) untuk Berbagi Informasi dan Pengaturan Grup pada Media Sosial Hasktag - Fanpula, Titus Sutio (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
The hashtag (#) system for sharing information and group settings on hasktag social media is a system that can be used to share information using hashtags. The system also allows users to not only use hashtags in sharing information, but can also be used to group some people who have the same intent and purpose commonly called group hasktag. From the results of tests conducted on the system that has been made, the test results obtained is the features that exist on the system that made has functioned in accordance with the expected, it just needs to be improved or need to be improved in order to provide maximum results when used by people Others who still do not understand about technology though